Assessing Student and Coach Learning Experiences with Virtual Collegiate Soil Judging Contest during COVID-19 Pandemic - Ammar B. Bhandari; Steven Chumbley; Benjamin Turner (MDPI AG, 2023)
Collegiate soil judging competitions are organized as annual face-to-face events both regionally and nationally in the USA. Soil judging provides a competitive platform for students to identify and describe soil characteristics in the field. However, the COVID-19 pandemic forced soil judging contests to find new strategies to maintain student engagement and provide competitive opportunities for students to apply their knowledge of soils. In response, Region IV in the USA hosted a virtual regional contest in October 2020. The objectives of this study were to quantify students' and coaches' perspectives on virtual soil judging contests and evaluate the role of virtual soil judging contests as either a complement or alternative to in-person contests. We conducted post-contest surveys of students (n = 31; 86% response rate) and coaches (n = 6, 100% response rate) to assess student learning outcomes and reflections on the virtual soil judging contest. Students responded most favorably to the virtual format, citing the flexibility it provided. Coaches were satisfied with the virtual format but still preferred an in-person contest. Coaches also expressed concern that the virtual soil judging format would not accurately measure the full range of student's skills typically measured during in-person contests. Overall, the coaches and students reported that the virtual soil judging contest was helpful to gain experience with soil descriptions and enhance skills related to soil assessment and pedology. We conclude that virtual soil judging contest formats can be an inexpensive way to provide students with additional soil judging experiences when field-based formats are not feasible (e.g., health restrictions such as COVID-19) or economical (e.g., budget constraints on soil site selection, contest development, and travel), and that hybrid formats may be a way to encourage greater participation among students in soil judging contests without losing the in-person benefits gained by judging soils in the field.